Study of a similarity boundary layer equation by using the shooting method (Letters in Nonlinear Analysis and its Applications, 2025)
In this paper we are interested in the study of the existence or nonexistence and uniqueness or nonuniqueness of the solutions of the boundary value problem involving a third order ordinary nonlinear autonomous differential equation satisfying a boundary conditions. Its solutions are the similarity solutions of a problem of boundary-layer theory.